THE CONCEPT OF GIRLS EDUCATION IN ISLAMIC PERSPECTIVE - Zailani Zailani; Safriyandi Barus; Muhammad Suganda Triadi (Proceeding International Seminar of Islamic Studies, 2021)
In this study the author tries to research and examine how the concept of girls education in Islamic perspective especially from the Al-quran, As-sunnah and books inherited by previous scholars who are now starting to disappear and even no longer applied in life, whereas in modern times there are many problems related to girls education. Islamic moral declarations and others.As an effort to restore the method of the education system presented by ldlam for girls so that they are not separated from high moral values and have a moral character to from a future generation of superior, intelligent, quality women, namely a generation with an idealistic personality with broad mastery and mastering the (science of life technology) is adequate. From the research it is known that in educating girls a lot involes various institutions and circles such as the home environment and the school environment in supervising the education of parents, teacher and others. In order to improve the quality of morals and knowledge and they will better understand how to dress in syari and how to get along in accordance with Islamic law. Wen schools, homes, teachers and parents apply the values presented by islam properly and correctly. To girls. Then girls will be able to face the challenges of the times in the future.Keywords: the concept, education, girl, Islamic perspective